The Impact of Fiscal Changes on the Economic Growth of the Lao PDR - SIRIVONG, Chansouk (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This study analyses the impact of fiscal reforms on economic growth in Laos during the period 2001-2024. To examine both the scale and sustainability of fiscal policy, the analysis draws on annual time-series data from the World Bank's world development indicators, focusing on two main fiscal measures: real government expenditure (RGE) and primary balance (PB). The study applies OLS regression to investigate quantitative associations between fiscal variables and GDP growth, complemented with Granger causality tests for determining the causation. The empirical results reveal that real government spending has a positive but statistically insignificant effect on economic growth and it suggests that ‘size does not matter’ for growth in the absence of efficient and allocative effectiveness. On the other hand, the primary balance has positive and significant impact, it implied that thriftiness as well as maintaining low leverages are important for long-term growth. Based on Granger causality tests, two-way causality between government spending and economic growth is confirmed in accordance with the Keynesian and Wagnerian views. This implies that in Lao PDR, fiscal policy has been focused more on growth and stabilizing the economy. The results reveal the need for a more rules-based fiscal framework to bring more stability and effectiveness. Policy recommendations include streamlining spending, raising money the government gets from its own citizens, concentrating on public investments that will pay off in the long-run and ensuring that public finances are managed transparently and accountably.